Unseen and unheard: African children with cancer are consistently excluded from clinical trials - Amoako, Emmanuella; Jumbam, Desmond Tanko; Bediako, Yaw (BMjJ Glob Health, 2021)
No abstract
Keywords: Cancer; University of Ghana; WACCBIP_NCDS; Black children